French victory in the siege of Château Gaillard in 1204 (engraving) - Auteur inconnu (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: French victory in the siege of Château Gaillard in 1204 (engraving). French victory in the siege of Château Gaillard in 1204 (engraving)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; Iconographie